DIGITAL MARKETING IN THE PRACTICE OF SMALL AND MEDIUM ENTERPRISES IN THE REPUBLIC OF MOLDOVA - Valeri GAGAUZ (Economy and Sociology, 2020)
The use of modern marketing strategies for small and medium-sized enterprises (SMEs) is an important factor that can contribute to strengthening entrepreneurial activity, qualitative structural changes to SMEs, and ensuring business sustainability and stability. The digital revolution and technologies open up new opportunities for the business sector, improving the quality of communication with customers, while digital marketing (DM) is an important tool that can ensure the competitiveness and effectiveness of actions taken to promote products and services. This article presents the results of a qualitative study of the perception and practice of SMEs in the field of DM conducted by the author in 2019. Twenty entrepreneurs – SME owners in Chisinau were interviewed. The analysis also includes a case study of the BRAVO-MOTORS company practice. The theoretical and conceptual framework of the study is comprised of modern marketing theory, ResourceBased View approach (Wernerelt B.) and Theory of dynamic capabilities (Teece et al.). The results of the study showed that SMEs do not pay due attention to digitalization of business processes, data collection and analysis, optimization of work processes and monitoring of key indicators. The role and importance of developing a marketing strategy is in many cases underestimated, and marketing activities are limited to the use of individual marketing elements only. There is a low level of competence of entrepreneurs in the field of marketing, especially regarding modern marketing tactics and strategies, as well as the lack of an integrated approach to the strategy of promotion and development of the company.